GIS-based coupled cellular automaton model to allocate irrigated agriculture land use in the High Plains Aquifer Region - Wang, Peiwen (Kansas State University, 2013)
The Kansas High Plains region is a key global agricultural production center (U.S. G.S, 2009). The High Plains physiography is ideal agricultural production landscape except for the semi-arid climate. Consequently, farmers mine vast groundwater resources from the High Plains Ogallala Aquifer formations to augment precipitation for crop production. Growing global population, current policy and subsidy programs, declining aquifer levels coupled with regional climatic changes call into question both short-term and long-term resilience of this agrarian landscape and food and water security. This project proposes a means to simulate future irrigated agriculture land use and crop cover patterns in the Kansas High Plains Aquifer region based on coupled modeling results from ongoing research at Kansas State University. A Cellular Automata (CA) modeling framework is used to simulate potential land use distribution, based on coupled modeling results from groundwater, economic, and crop models. The CA approach considers existing infrastructure resources, industrial and commercial systems, existing land use patterns, and suitability modeling results for agricultural production. The results of the distribution of irrigated land produced from the CA model provide necessary variable inputs for the next temporal coupled modeling iteration. For example, the groundwater model estimates water availability in saturated thickness and depth to water. The economic model projects which crops will be grown based on water availability and commodity prices at a county scale. The crop model estimates potential yield of a crop under specific soil, climate and growing conditions which further informs the economic model providing an estimate of profit, which informs regional economic and population models. Integrating the CA model into the coupled modeling system provides a key linkage to simulate spatial patterns of irrigated land use and crop type land cover based on coupled model results. Implementing the CA model in GIS offers visualization of coupled model components and results as well as the CA model land use and land cover. The project outcome hopes to afford decision-makers, including farmers, the ability to use the actual landscape data and the developed coupled modeling framework to strategically inform decisions with long-term resiliency.
Keywords: High Plains Aquifer; Irrigated agriculture land use; GIS; Coupled modeling; Cellular automaton model; OpenMI; Interdisciplinary modeling; Geographic Information Science and Geodesy (0370); Landscape Architecture (0390); Land Use Planning (0536); Water Resource Management (0595)